Epulis due to occlusion trauma, a combination surgery of excision and open flap debridement : A case report - Chandra, Adelia; Fitriani, Juli; Afrini, Nurul; Oktawati, Sri (Hasanuddin University, 2024)
Introduction : Gingival Enlargement can happen due to variable reasons, one of them being occlusion trauma (biting), this is due to the fact that the enlargement happened as a trauma response from chronic irritation. One of the main concerns of epulis in the anterior region is the potential of exacerbated conditions due to repeated contact, thus causing further inflammation in which will cause bone damage, furthermore aesthetic is also a concern as it discernible as it is located in the smile area of the patient. Case Report : A 30 year old female patient was presented to Hasanuddin Dental Hospital due to swollen gum in the lower front teeth, patient also complained that it bleeds easily. Patient stated that the swelling happened when the patient was eating an apple and the patient’s gum was torn from biting and was exacerbated when the incident happened again when eating, during which the swelling happened. Patient first visited a health facility before being referred and was given antibiotics, during which the gum is still bleeding and even bled during normal conversation. Patient routinely visited the dentist and last visited 3 months ago for Scalling, furthermore patients denied any systemic diseases and allergies. Conclusion : Epulis should be handled immediately with excisional surgery, furthermore, upon finding bone defects in the overgrown area, surgical debridement should be done as to prevent further damage to the alveolar structure in order to circumvent potential tooth mobility